Application of Point Sampling Method in Estimation of Stand Basal Area in Community Forest - Mulyana, Budi; Rohman, Rohman; Purwanto, Ris Hadi (Journal of Sylva Indonesiana, 2018)
Estimation of the potency of community forest is usually done with the census approach for each forest. Sampling methods to estimate the potency of community forest are still rare. The size of community forest is relatively small, scatter, and less irregular shape, therefore the estimation of community forest potency using sampling plot is difficult to apply. The approach of sampling without a plot (plotless/ point sampling) was cheaper and faster compare to the method of sample plots and direct measurement (census) in predicting basal area. The objective of this research is determining the difference in the average value of basal area using direct measurement of stand (census) and point sampling methods. The research was carried out for 4 months in 30 community forests at Kemuning Village, Gunungkidul District. Materials used to estimate basal area with point sampling method were Spiegel Relascope and Bitterlich Stick with the value of Basal Area Factor 1. Parameters measured were diameter at breast high (dbh) for census method and the number of trees were categorized in or border for point sampling method. The result was analyzed statistically using unpaired t-student. The result showed that the average of basal area of tree in community forest with point sampling method were no significantly different from the average of basal area with census method (Î± = 1%). Therefore, the point sampling method can be considered as a tool in inventory at community forest